A relational embeddedness perspective on dynamic capabilities: a grounded investigation of buyer-supplier routines - Alinaghian, Leila; Kim, Yusoon; Srai, Jagjit Singh (Elsevier, 2019)
Our study extends the emerging inter-firm-level theorization of dynamic capabilities by articulating how firms can develop and adapt their resource bases through supplier relations. Specifically, we aim to explore how different embedded relational aspects function together or separately to induce various inter-firm routines that presumably underpin the buying firm’s dynamic capabilities. The research design is a multiple case study involving 34 buyer-supplier dyad-level innovation events across six product groups of three multinational buying firms in the Pharmaceuticals, Aerospace, and Fast-Moving Consumer Goods sectors. Our inductive analysis suggests that the social, cognitive, and physical aspects of relational embeddedness play roles, in a cumulatively sequential fashion, in inducing three distinctive routine types—unilateral, quasi-unilateral, and bilateral—in the buyer-supplier dyads that underpin the three clusters of dynamic capabilities—sensing, seizing, and transforming, respectively. Furthermore, our study identifies two contingencies that explain variances in the observations and inferences. We therefore investigate the ‘black box’ of dynamic capabilities in inter-firm contexts, elucidating the roles and association of relational embeddedness and patterned activities (routines) in these relationships.
Keywords: Buyer-supplier relationship; Dynamic capabilities; Inter-firm routines; Relational embeddedness; Case studies